82.2k views
5 votes
Inga is solving 2x2 + 12x – 3 = 0. Which steps could she use to solve the quadratic equation? Check all that apply. 2(x2 + 6x + 9) = 3 + 18 2(x2 + 6x) = –3 2(x2 + 6x) = 3 x + 3 = 2(x2 + 6x + 9) = –3 + 9 (x + 3)2 =

User Lock
by
6.1k points

2 Answers

3 votes

Step 1,3 ,4 are the answers in edgenuit

User Diogojme
by
5.1k points
3 votes

Answer: The required steps are,


2(x^2+6x)=3


2(x^2+6x+9)=3+18

Explanation:

Here, the given quadratic equation is,


2x^2+12x-3=0

For solving the above equation, the steps are as follow,

Step 1 :


2x^2+12x-3=0

Step 2 :


2x^2+12x=3

Step 3 :


2(x^2+6x) =3

Step 4 :


2(x^2+6x+9)=3+18

Step 5 :


(x+3)^2=(21)/(2)

Step 6 :


x+3=\pm \sqrt{(21)/(2)}

Step 7 :


x=-3 \pm \sqrt{(21)/(2)}

Thus, by the above explanation we can find out the equations that will be used to solve the given quadratic equation.

User Nazmul Haque
by
5.5k points